Use of activity-oriented questions in qualitative focus group discussions to explore youth violence in Sindh, Pakistan - Hussain Maqbool Ahmed Khuwaja; Rozina Karmaliani; Judith McFarlane; Rachel Jewkes (Tehran University of Medical Sciences, 2019)
This paper reports the use of activity-oriented focus group discussions in a study that aimed to explore perceptions of youth violence among school-age adolescents of grade 6 to 8 in Pakistan. To engage students in active participation during focus group discussions, questions were asked in the form of activities like free listing, ranking, role-playing, and drawing. This paper explains how activity-oriented methods can help in the process of asking questions and retrieving information from adolescents to best energize the participants for optimum information. Furthermore, we explain the method of merging data from the activity-oriented questions for analysis and optimum understanding of participants' perspectives.